IMPROVING LISTENING SKILLS THROUGH PROJECT BASED LEARNING AND NATIVE SPEAKERS AS LEARNING SOURCES IN MASTERING VOCABULARY AND SENTENCE COMPREHENSION - Febriani, Suci Ramadhanti; Husna, Ilya; Yasmadi, Yasmadi; Refdianti, Afrina; Mela, Desriliwa Ade; Bedra, Kddour Guettaoui (UIN Sumatera Utara Medan, 2024)
This research aims to analyze students' listening skills through project-based learning and native speakers as learning resources in higher education. This research uses a mixed research design with a quantitative and qualitative approach to test the effectiveness of learning listening skills using project-based learning. This research used a sample of 71 students studying listening skills at UIN Imam Bonjol Padang in the Arabic Language Education study program. The research results show that; 1) The effectiveness of using project-based learning in listening shows a significant increase; 2) Listening skills using project-based learning are identified as including understanding in identifying sounds, words and sentences and students are able to produce the speech they listen to through elaboration of listening and speaking skills using digital platforms. This research confirms that the use of project-based learning can improve student skills with an average increase from 69.3 to 74.7. Meanwhile, the implication in learning to listen is increasing ability in vocabulary and mastery of Arabic sentences.